Volatility linkages between energy and food prices: Case of selected Asian countries - Farhad Taghizadeh-Hesary; Ehsan Rasoulinezhad; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2018)
This study examines the linkages between energy price and food prices over the period 2000-2016 by using a Panel-VAR model in the case of eight Asian economies, namely Bangladesh, the PRC, Indonesia, India, Japan, Sri Lanka, Thailand, and Viet Nam. Our results confirm that energy price (oil price) has a significant impact on food prices. According to the results of impulse response functions, agricultural food prices respond positively to any shock from oil prices. Furthermore, the findings from variance decomposition reveal that shares of oil prices in agricultural food price volatilities are the largest. In the second period 4.81%, and in the 20th period 62.49%, of food price variance is explained by oil price movements. The paper opens up new policy insight. Since inflation in oil price is harmful for food security, particularly in vulnerable economies, it would be necessary to diversify the energy consumption in this sector, from too much reliance on fossil fuels to an optimal combination of renewable and nonrenewable energy resources. In addition, the paper found that the impact of biofuel prices on food prices is statistically significant but explains less than 2% of the food price variance. However, by increasing the demand for biofuel, especially in advanced countries, there should be more concern about the global increase in agricultural commodities prices and endangering food security, especially in vulnerable economies.
Keywords: O13; Q41; Q11; Q18; 330; oil price; food price; agricultural commodities prices; Panel-VAR model